The Role of Protein Persulfidation in Brain Aging and Neurodegeneration - Petrovic, Dunja; Kouroussis, Emilia; Vignane, Thibaut; Filipovic, Milos R. (Frontiers in Aging Neuroscience, 2021)
Hydrogen sulfide (H2S), originally considered a toxic gas, is now a recognized gasotransmitter. Numerous studies have revealed the role of H2S as a redox signaling molecule that controls important physiological/pathophysiological functions. The underlying mechanism postulated to serve as an explanation of these effects is protein persulfidation (P-SSH, also known as S-sulfhydration), an oxidative posttranslational modification of cysteine thiols. Protein persulfidation has remained understudied due to its instability and chemical reactivity similar to other cysteine modifications, making it very difficult to selectively label. Recent developments of persulfide labeling techniques have started unraveling the role of this modification in (patho)physiology. PSSH levels are important for the cellular defense against oxidative injury, albeit they decrease with aging, leaving proteins vulnerable to oxidative damage. Aging is one of the main risk factors for many neurodegenerative diseases. Persulfidation has been shown to be dysregulated in Parkinson's, Alzheimer's, Huntington's disease, and Spinocerebellar ataxia 3. This article reviews the latest discoveries that link protein persulfidation, aging and neurodegeneration, and provides future directions for this research field that could result in development of targeted drug design.